2019
DOI: 10.1038/s41598-019-50436-1
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative Circulating Plasma Gelsolin Predicts Residual Disease and Detects Early Stage Ovarian Cancer

Abstract: Ovarian cancer (OVCA) patients with suboptimal residual disease (RD) and advanced stages have poor survival. pGSN is an actin binding protein which protects OVCA cells from cisplatin-induced death. There is an urgent need to discover reliable biomarkers to optimize individualized treatment recommendations. 99 plasma samples with pre-determined CA125 were collected from OVCA patients and pGSN assayed using sandwich-based ELISA. Associations between CA125, pGSN and clinicopathological parameters were examined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Importantly, plasma gelsolin is a powerful modulator of inflammation, which carries a protective function (DiNubile, 2008; Li et al, 2012). Low plasma gelsolin is a marker of poor prognosis in various pathological conditions, including diabetes (Khatri et al, 2014), cancers (Asare-Werehene et al, 2019; Stock et al, 2015) and sepsis (Lee et al, 2007), leading to suggestions and animal tests for its therapeutic use. Going forward, it will be important to assess GSN levels in at-risk populations for severe COVID-19, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, plasma gelsolin is a powerful modulator of inflammation, which carries a protective function (DiNubile, 2008; Li et al, 2012). Low plasma gelsolin is a marker of poor prognosis in various pathological conditions, including diabetes (Khatri et al, 2014), cancers (Asare-Werehene et al, 2019; Stock et al, 2015) and sepsis (Lee et al, 2007), leading to suggestions and animal tests for its therapeutic use. Going forward, it will be important to assess GSN levels in at-risk populations for severe COVID-19, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies in human oral carcinoma cells further elucidated the role of GSN in promoting apoptosis, cell proliferation, and enhancing tumor invasion and metastasis [44]. The ability of GSN to confer chemo-and radio-resistance has been reported in NSCLC, ovarian cancer, and HNSCC, all indicating that higher levels of GSN are associated with a higher risk of developing treatment resistance [17,18,45,46]. We report here, for the rst time, that the levels of GSN increase by 2.4 to 4.0 fold in the worst responding patients within 48 hours, which is maintained till 1 week of RT.…”
Section: Discussionmentioning
confidence: 99%
“…Asare-Werehene and colleagues [38] recently demonstrated that exosomal pGSN could promote the survival of ovarian cancer cells through both autocrine and paracrine stimulation and thereby confer chemoresistance. Moreover, preoperative circulating pGSN was found to be a favorable biomarker for early ovarian cancer detection, residual disease prediction, and overall prognosis [39]. Chen et al [40] also reported that serum pGSN levels were significantly lower in patients with colon cancer than in healthy controls and that pGSN could serve as a more effective diagnostic biomarker for colon cancer compared with the currently used carcinoembryonic antigen.…”
Section: Discussionmentioning
confidence: 99%